(untitled) - Barbosa-Cánovas, Gustavo V. (Rome, 2005)
This manual provides information on freezing technology to preserve fruits and vegetables in small-scale operations. Practical examples demonstrating the application of the technology are given to provide a better understanding of the processes. Compared to other conventional methods used in the storage of fruits and vegetables, freezing is the most satisfactory method in terms of quality, process and overall cost. Currently, the frozen food market is one the largest sectors in the food industry. Industrialized countries dominate the trade in frozen food commodities, but developing countries can also develop their own frozen food industries. Introduction of adequate freezing technology is essential to meet the growing consumer demand for frozen foods in developing countries.
Keywords: Frozen foods,Thực phẩm đông lạnh